The synthetic cannabinoid WIN55, 212-2 mesylate decreases the production of inflammatory mediators in rheumatoid arthritis synovial fibroblasts by activating CB2, TRPV1, TRPA1 and yet unidentified receptor targets. Issue 1 (December 2016) - Lowin, Torsten; Pongratz, Georg; Straub, Rainer
Abstract Background In rheumatoid arthritis (RA), synovial fibroblasts (SF) secrete large amounts of IL-6, IL-8 and matrix metalloproteinases (MMPs) which are crucial for cartilage destruction. RASFs are sensitive to the action of cannabinoids and they not only express cannabinoid receptors type I and II (CB1 and CB2 ) but also transient receptor potential channels type vanilloid (TRPV1) and ankyrin (TRPA1). The synthetic cannabinoid WIN55, 212-2 mesylate (WIN) demonstrated strong anti-inflammatory effects in monocytes and synovial fibroblasts only in high concentrations in a non-cannabinoid receptor dependent manner. In this study we assessed the ability of WIN to modulate cytokine and MMP-3 production in SFs over a wide concentration range and identified specific receptor targets that mediate the effects of this synthetic cannabinoid. Methods MMP-3, IL-6 and IL-8 were determined by ELISA. Adhesion was measured by the XCELLigence system. Proliferation was assessed by cell titer blue assays. Results WIN significantly reduced TNF-induced IL-6, IL-8 and MMP-3 production in concentrations below 2 μM, while higher concentrations completely inhibited production of IL-6 and IL-8 but increased extracellular MMP-3 levels. The inhibitory effect at low concentrations (<2 μM) was independent on activation of either CB1 or CB2 but was attenuated by TRPV1 or TRPA1 inhibition in OASFs and RASFs. The effects of high concentrations of WIN on cytokine and MMP-3 production were decreased by the calcium chelating agent BAPTA, the AMPK activator metformin, the TRPA1 antagonist A967079 and the CB2 antagonist COR170. Furthermore, fetal calf serum content in culture media strongly influenced the efficacy of WIN at high concentrations. In addition, high concentrations of WIN also diminished SF adhesion and proliferation without altering cell viability whereas low concentrations promoted SF adhesion without any influence on proliferation. Conclusion The synthetic cannabinoid WIN in low concentrations exhibits anti-inflammatory effects in synovial fibroblasts independent of CB1 and CB2 while CB2 and yet unidentified receptor targets are responsible for WIN effects in micromolar concentrations. Our results indicate a TRPV1/TRPA1 dependent mechanism of SF regulation that might be coupled to cellular energy status and calcium content.